Development and FEM Modeling of a New Severe Plastic Deformation Process according to the Reverse Shear Scheme. (16th October 2019) - Tarasov, Alexander F.; Altukhov, Alexander V.; Gribkov, Eduard P.; Abdulov, Aleksandr R.
Abstract : Industrial commercial use of SPD processes is in some cases hindered by the complexity of equipment and high loads on the tool associated with high hydrostatics upon implementation of existing deformation processes. New and modified SPD schemes are offered relatively often, so the methods for their creation, modeling, and ways of improvement are of particular interest. Therefore, the article provides a classification of SPD schemes, which are divided into several groups depending on the nature of the material flow in the deformation zone. The second attribute of the fission process is the volume of the metal, contemporaneously located in the plastic deformation zone. An analysis of the influence of SPD schemes on the features of formation of a plastic deformation zone allows us to identify promising ways to modify them. A new SPD process is proposed, called as the "Reverse Shear" (RS), in which the workpiece is deformed under conditions of flat deformed state, uniform in each cross section along the entire length of the workpiece. The RS process allows us to change the paths of deformation to redistribute strain within the workpiece volume due to different positioning of a workpiece in a die. To justify the proposed deformation scheme, the SPD processes are divided into groups and an analysis of the deformation schemes' features, which are analogs of RS, is performed. Simulation of the considered SPD processes was performed using FEM, implemented in specialized QForm CAE-system. A study of the influence of a tool with inclined surfaces on formation of a deformation zone in a workpiece during RS and analogues has been carried out. The degree of deformation nonuniformity in a cross section for the considered deformation schemes has been determined, and the possibilities of the proposed process are shown in comparison with analogues. The advantage of the RS scheme is the absence of unformed edges of the workpiece, which reduces material consumption, increasing the accumulated degree of deformation by one operation and reducing the tooling complexity to obtain workpieces with a desired structure. It also provides an opportunity to deform workpieces by various routes (RS-60 and RS-180) and to more specifically develop or select SPD schemes based on modeling. Changing the aspect ratio of the workpiece cross section also allows us to manage the change in its stress-strain state during deformation. Comparisons with the experiment carried out for three operations of deformation of a Cu-ETP copper sample by the RS-60 route show that the simulation results correspond to the real process.